THE ROLE OF ORGANIZATIONAL CULTURE, ORGANIZATIONAL JUSTICE, AND EMPLOYEE EMPOWERMENT IN INCREASING ORGANIZATIONAL COMMITMENT - Nurul Indriyani; Suhana Suhana (SEAN Institute, 2023)
This research was conducted with the aim of describing and analyzing the influence of organizational culture, organizational justice, and employee empowerment on organizational commitment at PT BPR BKK Demak. The type of data used is primary data, namely data obtained directly from the original source in the form of a questionnaire. Sampling was carried out with a population in this study exceeding 100 people, so this sampling technique used Quota Sampling, namely determining samples from populations that have certain characteristics to the desired number. The characteristics in question include: permanent employees whose working period is more than 1 year. The collected data were analyzed using factor analysis to test the validity of the question items, reliability testing using Cronbach Alpha, and hypothesis testing using multiple linear regression. The results showed that the organizational culture variable had no effect on organizational commitment, the organizational justice variable had an effect on organizational commitment, and the employee empowerment variable had no effect on organizational commitment